Phytochemical Profiling and Anti-Bacterial Activity of Red Delicious Apple Pomace With Integrated Hydrolysis to Obtain Fermentable Sugars: A Biorefinery Approach - Devi, Nisha; Cruz-Martins, Natália; Malik, Tabarak; Kumar, Vinod; Islam, Muhammad Torequl; Verma, Rachna; Singh, Gurvendra Pal; Kumar, Dinesh (Food science & nutrition, 2025)
Apple pomace (AP) is a byproduct of juice processing, rich in nutritionally important compounds like carbohydrates, phenolic compounds, dietary fiber, and minerals. It is a potential feedstock for sugar-based biorefineries. This study explored AP physicochemical and bioactive compounds and their hydrolysis to extract fermentable sugar. Results showed that AP had a below-neutral pH, moisture, acidity, and ash. The AP contained crude fiber (27.22%), total sugar (36.75%), and reduced sugar (12.22%). The extracts contained minerals like potassium, calcium, magnesium, aluminum, iron, boron, and zinc. A GC-MS study analyzed the phytochemicals present in AP extracts, revealing prominent antibacterial activity. The optimal conditions for enzymatic hydrolysis were found to be 1 mg/g substrate of cellulase and pectinase at 50°C and pH 5.0 at 24 h of incubation. Enzymatically hydrolyzed AP showed a high yield of reducing sugar (38.33%) compared to non-hydrolyzed AP (12.22%). The study suggests that AP, currently discarded as industrial bio-waste, is still a source of phytochemicals with significant antioxidant and antibacterial activities.
Keywords: polyphenols; biorefinery; apple pomace; enzymatic hydrolysis; antioxidant